Analysis of Speaking Methods in Teaching Foreign Languages - Abdujabarova, Kamola Husniddin Qizi (Journal of Higher Education and Academic Advancement, 2024)
The speed of reading may not be a leading indicator of the control in the first and second academic years. In subsequent classes, speed is the main indicator, along with content. The essence (task, purpose, role) of the control is now to consider what to check. A foreign language teacher gets a methodical problem of what to check. The object of investigation is thoroughly studied both theoretical and practical. The foreign language skills and skills learned by the teacher and administration are monitored. The extent to which learners have acquired the skills and abilities they have, what difficulties they have, and what to work hard on.